Enviornment : Chinese and American views - Laurence , J.C. Ma (ed.) (New York, 1981)
During the years from 1949 to 1977 very few American geographers visited China and no Chinese geographers visited the United States. In 1977 a group of American geographers, sponsored by the Ohio Academy of Sciences, visited China and in 1978 a ten-member delegation of Chinese geographers visited various American states to learn about American planning in theory and practice. In October 1978 a symposium, funded by the Johnson Foundation, was held in Racine, Wisconsin. This volume contains the material presented at this symposium. It demonstrates the wide range of scientific geographic investigation in the US and China, showing the concern of geographers in both countries for the physical and human environment.
Keywords: Human Ecology- Congresses